The Role of Literary Texts in Raising Learners’ Cultural Awareness - HAMAR, Soumia (My University, 2022)
The relationship between culture and language has been widely addressed by researchers and linguists. Besides, since literary works include representations and aspects of the target culture, reading and studying literature may contribute in some ways to enhancing the cultural awareness of readers and learners. This research works attempts to explore the role of literary texts as sources of the target language in raising EFL students’ cultural awareness. The study also aims to show the extent to which culture is represented through fiction, poetry, short fiction and other literary sub-genres. As the context of the study is EFL Algerian teritiary students, a questionnaire has been designed to explore their perceptions, understandings, and attitudes towards raising cultural awareness through reading literature. The population of this dissertation are third-year students at the English department, university of Mostaganem. The findings revealed that reading literary works contributes to a good extent to raising the students’ cultural awareness. Besides, the attitudes of the students seemed more positive towards and confirmative to the role that literature plays in representing cultural elements of the target language.
The Case of third-year EFL Students at Abdelhamid Ibn Badis University of Mostaganem
Keywords: literary texts; cultural awareness; literature; culture; EFL; Mostaganem university